Two new species of the Glyptosternine catfish genus Euchiloglanis (Teleostei: Sisoridae) from southwest China with redescriptions of E. davidi and E. kishinouyei - Zhou, Wei; Li, Xu; Thomson, Alfred W. (Zootaxa, 2011)
Two new species of the sisorid catfish genus Euchiloglanis are described from the upper Yangtze River and the upper Black River drainage (Red River basin) in China. Euchiloglanis longibarbatus n. sp. from the upper Yangtze River differs from E. davidi, E. kishinouyei and E. longus n. sp. by having an elongate and threadlike maxillary barbel with a pointed tip reaching posteriorly to beyond the gill opening. It differs from E. dorsoarcus by having the anal-fin origin closer to the caudal-fin base than to the pelvic-fin origin, and from E. phongthoensis by having the anus located midway between the pelvic-fin insertion and the anal-fin origin. Euchiloglanis longus n. sp. from the upper Black River drainage differs from E. davidi by having the length of the pectoral fin equal to 78.4–89.5% of the distance between the origins of the pectoral and pelvic fins, and from E. kishinouyei and E. longibarbatus n. sp. by having the distance between the origins of the pelvic and anal fins equal to 108.9–140.6% of the distance between the origins of the pectoral and pelvic fins. It further differs from E. davidi, E. kishinouyei, and E. longibarbatus n. sp. by having the depth of the caudal peduncle equal to 14.1–27.0% of the length of the caudal peduncle. It differs from E. dorsoarcus by having the anal-fin origin closer to the caudal-fin base than to the pelvic-fin origin, and from E. phongthoensis by having the distance from the adipose-fin origin to the dorsal-fin insertion equal to about 50% of the adipose-fin base length. Euchiloglanis davidi and E. kishinouyei are redescribed from recently collected specimens from their type localities. A lectotype is designated for E. davidi and a neotype designated for E. kishinouyei. Euchiloglanis kishinouyei is distinguished from E. davidi by lacking an indentation in the premaxillary tooth band, by having the length of the pectoral fin equal to 75.5–89.6% of the distance between the insertions of the pectoral and pelvic fins, and by having the distance between the insertion of the pelvic-fin and the anus equal to 81.5–97.5% of the distance between the insertions of the pectoral and pelvic fins. A key to the species of is Euchiloglanis also provided.